Analysis of Culture Shock Experienced by Foreign Students Studying in SMP Lab Undiksha in Academic Year of 2017/2018 - ., Putu Pendi Adnyana Putra; ., Prof. Dr. Ni Nyoman Padmadewi, M.A.; ., Dr. Ni Made Ratminingsih, M.A. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk mengetahui persepsi siswa asing terhadap culture shock dan menemukan cara untuk mengatasi masalah culture shock pada siswa asing yang belajar di SMP Lab Undiksha pada tahun ajaran 2017. Penelitian ini merupakan penelitian kualitatif deskriptif. Itu berlangsung di SMP Lab Undiksha. Ini menggunakan 3 instrumen yaitu: Observasi, kuesioner, dan panduan wawancara. Ada 4 subjek dalam penelitian ini. Hasil dari penelitian ini: 1) Ada sejumlah tekanan yang besar terhadap psikologis seperti depresi, kegelisahan, dan perasaan tidak berdaya, 2) Ada empat strategi yang diidentifikasi sebagai strategi untuk mengatasi culture shock seperti komunikasi, menemukan hal-hal yang tidak asing seperti di rumah dan berteman.Kata Kunci : persepsi siswa asing, culture shock, mengatasi culture shock This study was aimed to investigate the perceptions of foreign students toward culture shock and to find the way to cope with culture shock problems of foreign students who studied in SMP Lab Undiksha in academic year 2017. This study was a descriptive qualitative study. It took place in SMP Lab Undiksha. It used 3 instruments namely: Observation, questionnaire, and interview guide. There were 4 subjects in this study. The result of this study: 1) there was a large amount of psychological stress such as depression, anxiety, and feeling of helplessness, 2) there were three strategies identified as strategies to cope with culture shock such as communication, find familiar things as at home and making friends. keyword : Foreign student perception, culture shock, coping with culture shock